Tree management and environmental conditions affect coffee (Coffea arabica L.) bean quality. (1st December 2017) - Bote, Adugna Debela; Vos, Jan
Highlights: Under low nitrogen supply, organoleptic bean quality declines with increase in radiation level. In the absence of nitrogen limitation, quality attributes hardly respond to radiation. Fruit thinning and higher altitude improve coffee bean physical and organoleptic quality. Factors that support non-limiting supply of resources for beans to grow improve bean quality. Abstract: Coffees with specific taste and quality fetch higher prices. Although coffee plays a dominant role in the Ethiopian national economy, the country's coffee industry is generally characterized by low productivity and low quality. To address this issue, this study analysed the interactive effect of shade and nitrogen supply, fruit thinning and genotype by environment interactions on different coffee quality attributes. Organoleptic bean quality attributes declined with increase in radiation when nitrogen supply was limiting. In the absence of nitrogen limitation, however, the quality attributes hardly responded to radiation levels. In full sun, nitrogen had no effect on size and weight of coffee beans. Nitrogen supply improved bean size and weight at lower radiation levels. Fruit thinning and higher altitude significantly improved beverage quality, size and weight of coffee beans. Thinning beyond 50%, however, did not further improve the quality attributes. Effects of shade, nitrogen, fruit load and altitude are consistent with the proposition that organoleptic quality and the size of coffee beans are promoted by factors and conditions that support non-limiting supply of resources for beans to grow and by a sufficiently long period of maturation. Quality attributes did not differ much between varieties suggesting that crop management and growing environments may be more important determinants of quality than the genetic factors.